If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5n = 4n + 6 Reorder the terms: 5n = 6 + 4n Solving 5n = 6 + 4n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4n' to each side of the equation. 5n + -4n = 6 + 4n + -4n Combine like terms: 5n + -4n = 1n 1n = 6 + 4n + -4n Combine like terms: 4n + -4n = 0 1n = 6 + 0 1n = 6 Divide each side by '1'. n = 6 Simplifying n = 6
| 4+3r=16 | | 3x+1=12x+29 | | 6x-3=37-4x | | 3.14x4/3= | | -8+5c=6c | | 19-3j=7 | | 12x-8=62-2x | | z^2-7z= | | -2-4p=-7-5p | | -50.00+50x=300 | | (-9m+9)+(8m+8)= | | -q-5=4q | | -4-3m=19 | | (z-7)(z-7)= | | 5x-8=11+7x-2x | | (z-7)(z-7)=0 | | 2-27n=0 | | X+(x+2)+(x+4)=-15 | | 5x-8=11+7x-2 | | 0.75x+25=250.00 | | (X+1)(8x)=a | | 2(3x-3)=3(2x+2) | | 5y=-1x-3 | | r=2t+3 | | 8x=16+27 | | 2*(3x-8)+14=16 | | x*20/100=158 | | 2(3x-8)+14=16 | | x/6--1/x=1/3 | | x-20.7=9.5forx | | -8v=-9v+2 | | 7x-11=2(1-x) |